The Role of Pastoral Counseling Services in Spiritual and Psychological Recovery After Spontaneous Abortion - Gunarto, Rita Oktavia; Herman, Samuel; Hindradjat, Juliana (Indonesian Journal of Learning Education and Counseling, 2024)
Abortion is a condition where the fetus dies due to premature expulsion. Meanwhile, spontaneous abortion or miscarriage can occur without certain actions to trigger the expulsion of the fetus. Spontaneous abortions occur naturally, even when people maintain and want the fetus to grow. This results in physical disorders that have psychological impacts such as anxiety, easily giving up hope and an unsettled spirit. So it is very normal that everyone needs recovery after a spontaneous abortion. The role of a spiritual guide is very important in dealing with mental and spiritual recovery due to fetal loss. For this reason, pastoral counseling services guide the perspective of the Christian faith to find the true truth that will restore the soul. This article aims to provide understanding for Christians so that they can maintain a firm foundation of faith in facing every challenge in life such as spontaneous abortion. This research uses a qualitative approach by collecting data from various library sources, journals and the Bible as a source of truth and the basis of Christian faith.